Design and construction of cost saving solar irradiance data collection system - Soi, Sheng Leong (2019)
Photovoltaic system is one common alternative in reducing usage of fossil fuel to generate electricity. Photovoltaic system requires low cost of maintenance and is less location-dependent. However, the cost to install a photovoltaic system is relatively high. Furthermore, not all locations are suitable to build a photovoltaic system. Therefore, solar irradiance data is crucial in determining feasibility to install a photovoltaic system. In practical, solar irradiance data is collected using data logger and cannot be collected remotely. To tackle these problems, a cost saving irradiance data collection system which is able to perform solar tracking mechanism and IoT data collection, is designed and constructed. Arduino UNO was implemented as the core in performing solar tracking mechanism, while ESP32 was implemented as the core in performing IoT data collection system. In this project, LDRs were calibrated in order to achieve high precision in tracking the Sun. High precision current-to-voltage circuity for both pyrheliometer and pyranometer were constructed in order to achieve accurate current reading in ESP32, which will indirectly help in achieving high precision pyrheliometer and pyranometer. Low cost pyrheliometer and pyranometer were designed and constructed in this project. Extra features were included in this project. One of the features includes the initialization of solar tracker when the solar tracker is powered on. Another extra feature included was the ability of Blynk user interface platform in displaying the current status of solar tracker besides being able to display real-time solar irradiance data.